Targeted Mutagenesis in Plant Cells through Transformation of Sequence-Specific Nuclease mRNA - Stoddard, Thomas J. (PLoS One, 2016)
Plant genome engineering using sequence-specific nucleases (SSNs) promises to advance basic and applied plant research by enabling precise modification of endogenous genes. Whereas DNA is an effective means for delivering SSNs, DNA can integrate randomly into the plant genome, leading to unintentional gene inactivation. Further, prolonged expression of SSNs from DNA constructs can lead to the accumulation of off-target mutations. Here, we tested a new approach for SSN delivery to plant cells, namely transformation of messenger RNA (mRNA) encoding TAL effector nucleases (TALENs). mRNA delivery of a TALEN pair targeting the Nicotiana benthamiana ALS gene resulted in mutation frequencies of approximately 6% in comparison to DNA delivery, which resulted in mutation frequencies of 70.5%. mRNA delivery resulted in three-fold fewer insertions, and 76% were <10bp; in contrast, 88% of insertions generated through DNA delivery were >10bp. In an effort to increase mutation frequencies using mRNA, we fused several different 5’ and 3’ untranslated regions (UTRs) from Arabidopsis thaliana genes to the TALEN coding sequence. UTRs from an A. thaliana adenine nucleotide α hydrolases-like gene (At1G09740) enhanced mutation frequencies approximately two-fold, relative to a no-UTR control. These results indicate that mRNA can be used as a delivery vehicle for SSNs, and that manipulation of mRNA UTRs can influence efficiencies of genome editing.